Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1094/pdis-92-5-0800
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Residues of Diverse Plant Species by Gibberella zeae and Their Contribution to Fusarium Head Blight Inoculum

Abstract: The presence of Fusarium spp. was examined in the residues of wheat, barley, corn, sunflower, pasture, and gramineous weed species common in wheat and barley cropping systems collected from no-tillage and reduced-tillage plots from February 2001 to March 2003 in Uruguay. Gibberella zeae was recovered from residues of wheat, barley, corn, sunflower, fescue, and the gramineous weeds Digitaria sanguinalis, Setaria spp., Lolium multiflorum, and Cynodon dactylon, except from birdsfoot trefoil or white clover. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 18 publications
2
86
1
Order By: Relevance
“…graminearum has an epidemiological advantageit is able to produce perithecia and release ascospores. The production of ascospores is only possible when the soil moisture content is between 30% and 80%, and temperatures between about 7-10 and 15-20°C [11]. Fungi-colonized crop debris is one of the main sources of inoculum, as it provides a substrate for abundant sporulation during the next growing season.…”
Section: Introductionmentioning
confidence: 99%
“…graminearum has an epidemiological advantageit is able to produce perithecia and release ascospores. The production of ascospores is only possible when the soil moisture content is between 30% and 80%, and temperatures between about 7-10 and 15-20°C [11]. Fungi-colonized crop debris is one of the main sources of inoculum, as it provides a substrate for abundant sporulation during the next growing season.…”
Section: Introductionmentioning
confidence: 99%
“…FHB 15 epidemics are supported by cropping systems that leave high amount of crop debris 16 on the soil surface (Pereyra and Dill-Macky, 2008;Blandino et al, 2010) and 17 pathogens survive longer on residues that do not degrade easily, such as stem 18 nodes or stalks (Sutton, 1982). Thus, FHB disease and DON contamination are more…”
mentioning
confidence: 99%
“…In this study, two Plant-pathogenic fungal isolates of morphological were isolated from stems and roots of A.macrocephala. G. zeae is common Plant-pathogenic fungal in many species (Lee et al, 2009, Pereyra andDill-Macky, 2008) and we reported the phylogenetic significance of morphological character in the taxonomy of G. zeae species. However, F. lateritium is the dominant Pathogenic fungi firstly detected in A. macrocephala.…”
Section: Diversity Of Plant-pathogenic Fungal In This Studymentioning
confidence: 51%